A study of neonatal outcome in infants born to diabetic mothers at a tertiary care hospital - Anjum, Syeda Kausar; H. T., Yashodha (International Journal of Contemporary Pediatrics, 2018)
Background: Diabetes is the most common medical complication in pregnancy, affecting about 0.5-5% of all pregnancies. In developing countries, management of diabetes in pregnancy still poses a challenge. Infants of diabetic mother are at increased risk of periconceptional, fetal, neonatal and long-term complications. Methods: It was a prospective hospital-based study conducted in tertiary care hospital, Bangalore during a period of one year to assess the outcome in infants of diabetic mother and association of various complications to maternal glycemic status. Results: The incidence of diabetes in pregnant mothers in our hospital was 2.8%. Diabetic mothers with gestational diabetes mellitus (GDM) were 86 (86%) and with pre-gestational diabetes were 14 (14%). Various complications like hypoglycemia, hypocalcemia, polycythemia, hyperbilirubinemia, macrosomia, prematurity, respiratory distress syndrome, TTNB, congenital heart diseases were observed in infants of diabetic mothers. Among them hypoglycemia was the most commonly observed complication with frequency of 54%, followed by hypocalcemia which was seen in 43%, polycythemia in 35% and macrosomia in 15%. Significant association was found between various complications and glycemic control in mothers. Conclusions: High frequency of complications is seen in infants born to diabetic mothers. Hence, these babies should be delivered at hospitals where special neonatal care is available for management of high risks babies. Screening for GDMs should be performed in all pregnant women. Strict glycemic control in mother, planned pregnancy, proper antenatal care and strict monitoring in babies is required to prevent morbidity and mortality in infants of diabetic mother.